The real effect of foreign exchange hedging on corporate innovation. Issue 12 (18th August 2021) - Xia, Chongwu; Yang, Chuyi; Zhang, Lei
Abstract: We study the effects of foreign exchange hedging on corporate innovation. According to the information asymmetry hypothesis, corporate hedging reduces firms' information asymmetry, alleviates managers' career concerns, and helps investors better monitor managers, which enhances innovation. According to the market pressure hypothesis, hedging imposes short‐term earnings pressure on managers as a result of mark‐to‐market hedge accounting, discouraging innovation. Using 32, 194 observations of 5847 nonfinancial firms from 1998 to 2006, we document results that support the information asymmetry hypothesis . Hedged firms invest more heavily in innovative projects, generate more patents, and have more patent citations. To address endogeneity concerns, we employ both difference‐in‐differences and instrumental variable regressions and explicitly test for reverse causality.